Assessment of biodiversity, global distribution, and putative ecological niches of suessiacean dinoflagellates by DNA metabarcoding - Jang, Se Hyeon (Frontiers in Ecology and Evolution, 2022)
Dinoflagellates in the family Suessiaceae, so-called suessiacean dinoflagellates, play diverse roles in aquatic ecosystems, being distributed from tropical to polar waters and from marine to freshwater habitats and encompassing free-living forms, symbionts, and parasites. Despite their importance due to the variety of ecological roles and biodiversity, very few studies have characterized small suessiacean species. Recent advances in molecular techniques could provide insights into the yet unexplored ecological roles they play in aquatic environments. Using a global DNA metabarcoding dataset, this study elucidated the hidden biodiversity, global distribution, and ecological characteristics of suessiacean dinoflagellates. The results of this study indicated that the family Suessiaceae was the sixth highest in terms of read count and the ninth highest in terms of amplicon sequence variant (ASV) richness from a total of 42 categorized dinoflagellate families, suggesting that their global abundance has been greatly underestimated. Furthermore, metabarcodes of suessiacean dinoflagellates were found to be cosmopolitan in distribution, although the ecological niche of each taxon was distinctly different within the group based on their latitudinal and vertical distribution patterns. Moreover, phylogenetic analysis discovered at least five new phylogenetic groups and three new individual species within the family. Collectively, the findings of this study highlight the significance of suessiacean dinoflagellates in global aquatic ecosystems and reveal the importance of big data obtained from environmental DNA in exploring the ecological functions of understudied species.